Analysis of the Impact of Plastic Pollution on Environmental Accounting and Implementation of Blue Economy in the Coastal Area of ​​Serangan Beach, Bali - WEDANTARA, Ida Bagus Rai; DEWI, Kadek Ayu Kartika; CONSTANTIA, Putu Sri Devina; ARIAWAN, I Gede Dodik (PT Batara Swastika Harati, 2025)
This study analyzes the impact of plastic pollution on environmental accounting and the implementation of the blue economy in Serangan Beach, Bali. This descriptive qualitative study uses a literature review and semi-structured interviews with fishermen and MSMEs. The results show that plastic pollution in Serangan Beach has had a serious impact on the ecosystem, public health, and the local economy. Although the Bulan Cinta Laut (BCL) program has been launched, the implementation of environmental accounting is still not optimal. The implementation of the blue economy is also hampered by the imbalance in roles between local communities and industry players. This study concludes the need for cross-sector collaboration and a systematic recording system to overcome plastic pollution and support the implementation of a sustainable blue economy in Serangan Beach.